2000
DOI: 10.1007/s004240051012
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of angiotensin II on human erythropoietin production

Abstract: Current evidence suggests that angiotensin II may be involved in the regulation of renal erythropoietin (EPO) production. The present study assessed the role of angiotensin II (A II) in different doses in the control of EPO production in humans. In a parallel, randomized, placebo-controlled open design, 60 healthy male volunteers received a 6-h intravenous infusion of: placebo (placebo, electrolyte solution), a pressor dose of A II (1-3 microg/min; A II press), a combination of a pressor dose of A II and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
4
25
1
Order By: Relevance
“…The application of the AT1-receptor blocker losartan inhibited the rise of Epo levels, whereas ACE inhibitors did not [17,18]. Later, these findings were confirmed by others [19].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The application of the AT1-receptor blocker losartan inhibited the rise of Epo levels, whereas ACE inhibitors did not [17,18]. Later, these findings were confirmed by others [19].…”
Section: Introductionsupporting
confidence: 78%
“…This was regarded a clinically relevant change of Epo concentrations based on the results of our earlier studies [17,18]. The standard error was assumed to be 33%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Ang II has also been implicated in EPO regulation in vivo. Clinical studies of healthy human volunteers demonstrated that Ang II administration increased serum EPO concentration by ∼35% or higher via the activation of the angiotensin II type 1 receptor (AT 1 R) (Freudenthaler et al, 1999(Freudenthaler et al, , 2000Gossmann et al, 2001). Furthermore, the Ang II-converting enzyme inhibitors captopril and enalapril that block the maturation of Ang II from Ang I, significantly decreased plasma EPO levels, by as much as ∼20-30% in another study of healthy human volunteers (Pratt et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human volunteers demonstrated that elevation of plasma renin activity (PRA) and thus AII levels, as well as intravenous infusion of AII, elevated EPO concentrations in a dose-dependent manner. These effects were greatly reduced by administration of the AII receptor antagonist losartan (Freudenthaler et al, 1999a(Freudenthaler et al, , 2000Gossmann et al, 2001). However, alteration of endogenous angiotensin II levels following high-(HS) and low-salt (LS) diet showed no effect on EPO secretion in healthy volunteers (Freudenthaler et al, 2003), whereas high-salt diet increased EPO concentrations in essential hypertensive patients (Naomi et al, 1993).…”
mentioning
confidence: 99%